Putusan Open Legal Policy Ketentuan Tindak Pidana Zina Perspektif Maqashid Syariah - Amiruddin Hasan; Abid Rohmanu (Journal of Economics, Law, and Humanities, 2022)
Constitutional Court Decision No. 46/PUU-XIV/2016 which rejects the expansion of the meaning of adultery in the Criminal Code has become a hotly debated topic. Some people think that the Constitutional Court should have the courage to make legal breakthroughs on this very important issue. However, the Constitutional Court Justices are of the opinion that the expansion of the meaning of adultery is not within their jurisdiction. This type of research is a normative juridical research, with a statute approach. The nature of the research is descriptive analytical, using a knife of maqa>s{id sharī'ah concept analysis. From the results of the research, it was concluded that first, the contextualization of Jaseer Auda's maqa>s{id sharī'ah concept against the arguments of the Constitutional Court judges in family resilience was actually quite well represented. However, the judges tended to choose the cause of the damage to be more due to the existence of a void in the law, in which the authority to fill in the law could only be exercised by the Indonesian Legislation Body, namely the Indonesian House of Representatives. Second, LGBT are the most massive and dangerous implications indirectly in the decision of the open legal policy. In addition to the harm in the form of diseases caused by these actions, the threat of nasab (hifdz al-nasab) which is guarded by Islam itself and the tarnishing of honor that is contrary to Islamic teachings in order to maintain the honor of oneself and others (hifdz al-'irdh). Third, Realistic efforts to prevent cohabitation and the potential for violence against women, namely through the contemporary maqa>s{id system approach, include the following, namely by limiting the facilities that are feared to cause convenience in cohabitation behavior.